Ab initio quantum study of the photodynamics and absorption spectrum for the coupled 11A2 and 11B1 states of SO2 - Lévêque, Camille; Komainda, Adrian; Taïeb, Richard; Köppel, Horst (The journal of chemical physics, 2013)
The nonadiabatic photoinduced dynamics occurring in the coupled 11A2 and 11B1 excited states of SO2 is investigated using ab initio quantum dynamical methods. To this end, large scale calculations of the potential energy surfaces have been carried out at the multireference configuration interaction level. All vibrational degrees of freedom of the molecule are considered in the potential energy surface calculations and the quantum dynamical treatment. To deal with the symmetry-allowed conical intersection which occurs between the potential energy surfaces, we use the diabatic picture in the framework of regularized diabatic states. Wave-packet propagation on the coupled surfaces was performed and allowed to reproduce with good accuracy the complex absorption band observed experimentally in the 29 000-42 000 cm−1 range. This provides a basis for a subsequent theoretical treatment of the high order harmonic spectra of SO2.
Im Titel ist die Zahl "1" nach der ersten "1" hochgestellt
Im Titel ist die Zahl "2" nach dem Buchstabe "A" und nach dem Buchstabe "O" tiefgestellt
Im Titel ist die Zahl "1" nach dem Buchstabe "B" tiefgestellt
Gesehen am 16.02.2022